PTH-131 First Year Results from a Virtual Iron Deficiency Anaemia Service at a District General Hospital. (4th June 2013) - Shandro, B M; Basuroy, R; Gamble, L; Edwards, S; Al-Shamma, S; McLaughlin, S D
Abstract : Introduction: Iron deficiency anaemia (IDA) has a prevalence of up to 5% in adult men and post-menopausal women, and is a common cause of referral to gastroenterologists. Important and common causes of IDA to exclude include coeliac disease (5%), gastric carcinoma (5%) and colonic carcinoma (5–10%). Despite this, IDA is not an indication for fast track referral at our institution. Recently the British Society of Gastroenterology (BSG) published guidelines for the investigation of IDA suggesting that all patients need oesophagogastroduodenoscopy (OGD), colonoscopy or computerised tomography (CT), urinalysis, and coeliac serology or duodenal biopsy. By establishing a virtual IDA clinic we aimed to ensure that our patients received these investigations within 4 weeks, without unnecessary follow up in a formal clinic. Methods: All requests for investigation of IDA are vetted by a band 7 nurse, investigations arranged and the results followed up with consultant support. A prospective database is maintained, and we report our first year results. Fisher's exact test was used to compare the prevalence of cancer in this group to all fast track cases referred for endoscopy at our institution over the same period. Results: 467 patients were referred with IDA: 189 male, mean age 71. 100% received an OGD and 96% received either a colonoscopy (81%) or CT (15%). Mean waiting times from initial referral were 24 days to OGD, 32 days to colonoscopy, and 52 days to CT. 54% had documented urinalysis results, but all patients' GPs were sent a letter advising urinalysis. 98% were investigated for coeliac disease, with serology (2%), duodenal biopsy (57%), or both (39%). Carcinoma was diagnosed in 9.2% (1.5% upper gastrointestinal carcinoma (n = 7), 7% colonic carcinoma (n = 31), and 1% other malignancy (renal tract (n = 3), lung (n = 1), and pancreatic (n = 1))). Coeliac disease was diagnosed in 3%. A potential cause for IDA was found in 35% of patients. Notably, there was a higher prevalence of carcinoma in the IDA group (9.2%) than in the fast-track endoscopy group (6.6%), however this was not statistically significant (p = 0.08). Conclusion: The virtual IDA service at this district general hospital meets the audit standards recommended by the BSG (> 90% screened for coeliac disease and > 90% receiving both upper and lower GI investigation). There was no significant difference in the prevalence of cancer in IDA patients compared to patients referred for fast-track endoscopy. In view of the high cancer detection rate we plan to investigate all IDA patients within 2 weeks, and recommend that other centres consider doing the same. Disclosure of Interest: None Declared. Reference: Goddard AF, James MW, McIntyre AS, Scott BB; British Society of Gastroenterology. Guidelines for the management of iron deficiency anaemia. Gut. 2011 Oct; 60:1309–16